Nonsuicidal self-injury among adolescents with disorders of emotion and behavior: clinical characteristics and association with suicidality - Lero, Marija M; Živanović, Dušan; Mitković Vončina, Marija (Medicinski podmladak, 2019)
Abstract Introduction: Nonsuicidal self-injury (NSSI) is defined as a separate entity of the DSM-V classification of mental disorders, as a “condition for further study”. Although the NSSI is not driven by suicidal intention, studies do show its association with suicidal phenomena, but this relationship is still unclear. The aim: The aim of our paper was to examine the characteristics of the NSSI phenomenon among adolescents with disorders of emotion and behavior, with special emphasis on its association with suicidal behavior. Material and methods: The study included 100 older adolescents with depressive disorders, anxiety disorders, adjustment disorders and mixed disorders of conduct and emotion, who were treated in day hospital. The data was obtained from the existing medical records, and included information of NSSI and suicidal phenomena, psychiatric symptoms, diagnoses, rating scales for depression and global functioning, and data from personal and family history. Results: In our sample, the NSSI was more common in girls, and among younger adolescents. When it comes to clinical characteristics, this phenomenon was associated with higher depression symptom scores at admission and discharge, the presence of hypobulia-anhedonia, panic attacks, tension and restlessness, heteroaggressive manifestations, more frequent use of alcohol and borderline personality disorder. NSSI was also significantly associated with the presence of suicidal ideation during life, as well as with more severe suicidality level. Among NSSI patients, suicidal attempts were more common among those who were neglected in childhood, with younger age of maltreatment onset, those with lower global functioning on admission, with cognitive problems, and with problematic compliance at admission. Conclusion: High prevalence of NSSI in our sample, as well as numerous clinical features associated with it, may speak in favor of this phenomenon as a separate diagnostic entity. The observed association to suicide can be of clinical significance in terms of directing preventive steps. Keywords: nonsuicidal self-injury, self-harm, adolescents, suicidality